Biological Characteristics of Severe Combined Immunodeficient Mice Produced by CRISPR/Cas9-Mediated Rag2 and IL2rg Mutation - Zhao, Yong; Liu, Peijuan; Xin, Zhiqian; Shi, Changhong; Bai, Yinlan; Sun, Xiuxuan; Zhao, Ya; Wang, Xiaoya; Liu, Li; Zhao, Xuan; Chen, Zhinan; Zhang, Hai (Frontiers in Genetics, 2019)
Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas)9 is a novel and convenient gene editing system that can be used to construct genetically modified animals. Recombination activating gene 2 (Rag2) is a core component that is involved in the initiation of V(D)J recombination during T- and B-cells maturation. Separately, the interleukin-2 receptor gamma chain gene (IL2rg) encoded the protein-regulated activity of natural killer (NK) cells and shared common receptors of some cytokines. Rag2 and IL2rg mutations cause immune system disorders associated with T-, B-, NK cell function and some cytokine activities. In the present study, 2 single-guide RNAs targeted on Rag2 and IL2rg genes were microinjected into the zygotes of BALB/c mice with Cas9 messenger RNA to create Rag2/IL2rg−/− double knockout mice, and the biological characteristics of the mutated mice were subsequently analyzed. The results showed that CRISPR/Cas9-induced indel mutation displaced the frameshift of Rag2 and IL2rg genes, resulting in a decrease in the number of T-, B-, and NK cells and the destruction of immune-related tissues like the thymus and spleen. Mycobacterium tuberculosis 85B antigen could not induce cellular and humoral immune response in mice. However, this aberrant immune activity compromised the growth of several tumor heterogenous grafts in the mutated mice, including orthotopic and subcutaneous transplantation tumors. Thus, Rag2/IL2rg−/− knockout mice possessed features of severe combined immunodeficiency, which is an ideal model for human xenograft.